EFFECT OF POTASSIUM FERTILIZATION ON PHYSIOLOGYCAL, GROWTH, PHENOLOGY PERFORMANCE OF MUNG BEAN UNDER LOW WATER AVAILABILITY - Eka Kartina; Zavira Nurul Rachmaniar; Aep Wawan Irwan; Fiky Yulianto Wicaksono (UIN Sunan Gunung Djati Bandung, 2026)
Mung bean (Vigna radiata L.) is an important legume crop that plays a strategic role as a source of plant-based protein, a functional food ingredient, and an adaptive crop widely cultivated in various tropical and subtropical regions. Mung bean are a legume crop with high agronomic potential, mung bean productivity still faces several challenges, particularly due to climate change and rainfall patterns. These environmental changes can reduce water availability in agricultural lands and increase the risk of drought stress. Low water availability is one of the primary limiting factors in mung bean cultivation because it impedes overall plant performance, such as growth, phenological development, and physiological functions. Water deficit can disrupt plant biological processes through reduced tissue water status, impaired nutrient uptake and distribution, decreased metabolic activity, and increased oxidative stress, which eventually leads to reduced productivity. Under drought stress conditions, potassium (K) plays a crucial role as an essential nutrient that helps improve plant tolerance to water limitations. Potassium contributes to maintaining osmotic balance, improve water use efficiency, support physiological stability, and strengthening plant adaptation mechanisms against drought stress. Therefore, proper potassium management can be a potential strategy to improve mungbean resilience and maintain plant performance under low water availability conditions.